2016
DOI: 10.1186/s12918-016-0307-y
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding brain-gut-microbiome connections in Alzheimer’s disease

Abstract: BackgroundAlzheimer’s disease (AD) is complex, with genetic, epigenetic, and environmental factors contributing to disease susceptibility and progression. While significant progress has been made in understanding genetic, molecular, behavioral, and neurological aspects of AD, relatively little is known about which environmental factors are important in AD etiology and how they interact with genetic factors in the development of AD. Here, we propose a data-driven, hypotheses-free computational approach to chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
100
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 44 publications
2
100
0
1
Order By: Relevance
“…However, the exact mechanisms underlying how microbial metabolites regulate brain function have not been fully elucidated. A recent study proposed that TMAO is highly associated with Alzheimer's disease, which provides new insight into the influence of microbial metabolites on brain aging and cognitive function (Xu & Wang, 2016). In our research, we observed that TMAO could induce neuron senescence (Figure 3c and d) and destroy mitochondria in the hippocampal CA3 region of mice (Figure 4c and d), leading to aggravated brain aging in mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the exact mechanisms underlying how microbial metabolites regulate brain function have not been fully elucidated. A recent study proposed that TMAO is highly associated with Alzheimer's disease, which provides new insight into the influence of microbial metabolites on brain aging and cognitive function (Xu & Wang, 2016). In our research, we observed that TMAO could induce neuron senescence (Figure 3c and d) and destroy mitochondria in the hippocampal CA3 region of mice (Figure 4c and d), leading to aggravated brain aging in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, we observed that TMAO could induce neuron senescence (Figure 3c and d) and destroy mitochondria in the hippocampal CA3 region of mice (Figure 4c and d), leading to aggravated brain aging in mice. Recent studies demonstrated that elevating the circulating TMAO level could impair mitochondria and induce cardiovascular events (Xu & Wang, 2016). Mitochondrial energy metabolism impairments can decrease ATP production and increase calcium buffer damage and H 2 O 2 generation, which is considered a crucial player in both aging and neurodegenerative disorders (Johri, Chandra & Beal, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second paper, Xu and Wang developed a computational approach to characterize which and how human gut microbial metabolites may contribute to various aspects of Alzheimer's disease (AD), a disease that is currently under extensive investigation [3]. They found metabolites were significantly associated with various aspects of AD, such as AD susceptibility, cognitive decline, biomarkers, age of onset, and the onset of AD, which provided evidence to support that human gut microbial metabolites might serve as an important mechanistic link between environmental exposure and AD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The human microbiota is plausibly related to diseases such as type 2 diabetes (10), cardiovascular disease (11), irritable bowel syndrome (IBS) (12), and Crohn's disease (13) and some afflictions like obesity (14,15) and malnutrition (16), as well as many other diseases (17). Current studies have revealed that gut microbes also influence brain function and behavior and are related to neurological disorders like Alzheimer's disease through the gut-brain axis (18,19). Recently, chronic fatigue syndrome (CFS), a subtle but devastating condition often cited as a psychosomatic disease, has been associated with a reduced diversity and altered composition of the gut microbiome (20).…”
mentioning
confidence: 99%